Impact of seed producer cooperatives membership on technical efficiency: evidence from tef farmers in the central highlands of Ethiopia - Gemechu, Abera; Jaleta, Moti; Zemedu, Lemma; Beyene, Fekadu (Elsevier, 2025)
Farmers in Ethiopia face challenges associated with low efficiency and productivity, primarily due to limited access to improved seeds and complementary inputs. Despite empirical evidence of the vital role played by agricultural cooperatives in providing these basic inputs, there has been no empirical study examining the impact of membership in seed producer cooperatives (SPCs) on agricultural development. This study aimed to assess the impact of membership in SPC on the technical efficiency (TE) of farmers in the central highlands of Ethiopia. Using data from 425 selected tef farmers, the paper employed propensity score matching to match SPC members with non-members and applied a selectivity-corrected stochastic production frontier model to address unobserved biases. In addition, the meta-frontier approach was used to compare TE scores between the two groups of farmers. Results reveal that SPC members achieved a TE of 72 % of their potential output, whereas non-members achieved only 59 %. SPC members achieved meta technical efficiency (MTE) of 67 %, while non-members obtained MTE of 49 %. This indicates that non-members face tef production challenges due to limited access to improved technologies. In conclusion, SPC membership significantly enhances the TE of members compared to non-members indicating that improving TE could greatly boost productivity in the tef sector. The findings of the study suggest that the government of Ethiopia should enhance the skills of SPC members by providing training and promoting knowledge sharing among farmers to improve seed access. Similarly, private seed producers should be strengthened to meet the growing demand for improved seeds.